Taxonomic information on some Japanese Chironomidae (Diptera) described by Dr. M. Sasa (†) - Yamamoto, Nao; Yamamoto, Masaru (Zootaxa, 2018)
Holotypes of 19 species and non-type specimens preserved in the Sasa collection at The National Museum of Science, Tokyo, Japan, have been examined. Seventeen new synonyms are given, as follows: Paratrissocladius ogasaduodecimus Sasa et Suzuki, 1997 = Paraphaenocladius impensus (Walker, 1856); Bryophaenocladius togafelix Sasa et Okazawa, 1992, and B. toganitemus Sasa et Okazawa, 1992 = Pseudorthocladius togakileus Sasa et Okazawa, 1992; Bryophaenocladius togatenuis Sasa et Okazawa, 1992 of Smittia nudipennis (Goetghebuer, 1913); Chironomus daitoefeus Sasa et Suzuki, 2001 of C. circumdatus Kieffer, 1916; C. inaabeus Sasa, Kitami et Suzuki, 2001 = C. nippodorsalis Sasa, 1979; C. tokarabeceus Sasa et Suzuki, 1995 = C. okinawanus Hasegawa et Sasa, 1987; C. ginzanbeceus Sasa et Suzuki, 2001 = C. riparius Meigen, 1904; C. simantobeceus Sasa , Suzuki et Sakai, 1998 = C. claggi Tokunaga, 1964; C. echizensis Sasa, 1994 = C. yoshimatsui Martin et Sublette, 1972; Chironomus famiabeus Sasa, 1996, C. inabeceus Sasa, Kitami et Suzuki, 2001 and C. ginzanabeus Sasa et Suzuki, 2001 = Glyptotendipes biwasecundus Sasa et Kawai, 1987; Chironomus kagaensis Sasa, 1994 = Glyptotendipes tokunagai Sasa, 1979; Chironomus toyamabiceus Sasa, 1996 = Kiefferulus umbraticola Yamamoto, 1979; Microtendipes iriocedeus Sasa et Suzuki, 2000 of Polypedilum bingoparadoxum Kawai, Inoue et Imabayashi , 1998. The sufficient reason why Chironomus daitocedeus Sasa et Suzuki, 2001 should be treated as a junior synonym of C. javanus Kieffer, 1924 is shown. Two further species: Paratrissocladius sudagaicedeus Sasa et Tanaka, 2001 and Bryophaenocladius togatenellus Sasa et Okazawa, 1992 are transferred to Chaetocladius. Specimens from Okinawa, Miyako and Ishigaki Islands, originally reported as Rheocricotopus chalybeatus (Edwards, 1929) are identified as R. okifoveatus Sasa, 1990. A new species, Einfeldia sasai is described on the basis of specimens recorded from Minamidato Island, previously incorrectly determined as E. pagana.